Effect of Nitrogen Composition on Band Gap Energy and Photocatalytic Activity of TiO2-N/Zeolite Composite - Al Islam, Hanif Mufti; Sutisna, Sutisna; Rohman, Lutfi (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2025)
In this study, the application and performance of TiO2-N/Zeolite composites for MB photodegradation under UV irradiation have been reviewed. To improve the removal performance, the TiO2-N/Zeolite composite was varied based on the concentration ratio of urea to TiO2, where urea is a precursor of nitrogen. UV-Vis DRS tests were also carried out to compare and evaluate differences in band gap energy for each variant, analysis of degradation results and MB removal mechanisms by TiO2-N/Zeolite composites are described in this study. The aim of this research is to determine the effect of the urea to TiO2 concentration ratio (urea:TiO2), on the photocatalytic activity of the TiO2-N/Zeolite composite and also its physical characteristics, namely band gap energy. Thus, as a comparison, TiO2 and TiO2-N were also tested for photocatalytic activity and band gap energy physical characteristics. The conclusion obtained from this research is that the smaller the nitrogen composition in the TiO2-N/Zeolite composite, the greater the photocatalytic activity capability in degrading MB, in this case the TiO2-N/Zeolite (1.5) sample has the best photocatalytic activity. The next conclusion is that the higher the nitrogen composition in the TiO2-N/Zeolite composite, the smaller the band gap energy.